Hypertonic volume therapy: feasibility in the prevention and treatment of multiple organ failure and sepsis - Pacheco Jr., Adhemar Monteiro (1995)
Small-volume resuscitation by means of bolus infusion of hypertonic saline solutions was first applied for the primary treatment of severe hemorrhagic and traumatic shock and promptly restored central hemodynamics and regional organ blood flow. Mechanisms of action are diverse - i. maintenance of high cardiac output (direct myocardial stimulation; increase in intravascular volume); ii. maintenance of peripheral arterial vasodilation (effect of hyperosmolality; plasma volume effect) and iii. reduction of tissue edema (shifting of tissue water along the osmotic gradient). These mechanisms promote the restoration of the severely impaired microcirculation frequently seen also in sepsis. Hypertonic volume therapy has been the object of several experimental studies of acute hyperdynamic endotoxemia, however, a greater number of clinical studies have to be developed for the better understanding of the positive, and perhaps hazardous, effects of small-volume resuscitation in sepsis and multiple organ failure. The aim of this paper is to review the concepts involving such solutions, and their potential use in treatment of profound hypovolemia and microcirculatory deterioration associated with sepsis and endotoxic shock.